Childhood Poisoning - Associated Factors and Clinical Profile in a Tertiary Care Hospital - Parvin, Most Firoza; Ara, Chaman; Momotaj, Tanjila; Mia, Sanaul Haque; Uddin, Md Belal; Begum, Fardoushi; Rashid, Md Mamun Ur (TAJ: Journal of Teachers Association, 2023)
Background: Acute poisoning is a common medical emergency in the pediatric unit. It is a common preventable cause of morbidity and mortality in children. Most of the poisoning in children less than five years of age is accidental. This study aimed to determine the associated factors and clinical profile of childhood poisoning. Material & Methods: A cross-sectional descriptive study was carried out among 69 children aged six months to 12 years with a history of poisoning over six months. History, clinical examination, and details of the poisoning were obtained by using a structured questionnaire during admission. Analysis was done through standard statistical tests. Result: Among the 69 children of poisoning, 92.8% were accidental, and 7.2% were suicidal. Most cases (79.7%) were from the 6 - 59 months age group with male-female ratio 1.7:1. Most of the fathers (65.2%) and mothers (75.4%) had primary education, and 75.4% were poor. The most common cause of the poisoning was insecticide (60.9%), and the poison was stored at an available site (91.3%) in an unsealed container (47.8%). Accidental poisoning was more common in younger age group (<5 years) in male (70.31%) patients with normal family relationships (78.1%), whereas suicidal poisoning was more common in older age group (>10 years) in females (80%) patient with h/o familial disharmony (60%). Conclusion: Insecticides and kerosene were the common cause of poisoning. Most of the materials were stored in an unsafe place and stored in an attractive bottle. Poison should be stored in a safe home with a sealed container. Simple and active family preventive measures can reduce accidental poisoning. TAJ 2022; 35: No-2: 75-82